2022
DOI: 10.3390/healthcare10060978
|View full text |Cite
|
Sign up to set email alerts
|

Increased Wellbeing following Engagement in a Group Nature-Based Programme: The Green Gym Programme Delivered by the Conservation Volunteers

Abstract: The wellbeing benefits of engaging in a nature-based programme, delivered by the Voluntary, Community and Social Enterprise sector, were examined in this study. Prior to attending The Conservation Volunteers’ Green Gym™, attendees (n = 892) completed demographics, health characteristics and the Warwick Edinburgh Mental Wellbeing Short-Form Scale. Attendees (n = 253, 28.4%) provided a measure on average 4.5 months later. There were significant increases in wellbeing after engaging in Green Gym, with the greates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…All data collected at follow up points two, three and four was collected between August 2020 and January 2022, during the coronavirus pandemic. If the pandemic had not occurred it is possible that improvements in wellbeing would have continued or stabilised over time, in line with the research of Smyth et al [ 58 ] demonstrating sustained wellbeing increases after 13 months of attending nature-based volunteering programmes. However, it is important to note that neither male or female wellbeing returned to baseline values, despite the pandemic, and throughout the pandemic wellbeing scores decreased in the general population [ 32 ].…”
Section: Discussionmentioning
confidence: 56%
“…All data collected at follow up points two, three and four was collected between August 2020 and January 2022, during the coronavirus pandemic. If the pandemic had not occurred it is possible that improvements in wellbeing would have continued or stabilised over time, in line with the research of Smyth et al [ 58 ] demonstrating sustained wellbeing increases after 13 months of attending nature-based volunteering programmes. However, it is important to note that neither male or female wellbeing returned to baseline values, despite the pandemic, and throughout the pandemic wellbeing scores decreased in the general population [ 32 ].…”
Section: Discussionmentioning
confidence: 56%
“…It is also consistent with numerous previous studies that investigated the effects of forestry activities on the emotional recovery and wellbeing of the human body. In particular, in the case of the United Kingdom’s Green Gyms, a program in which residents participate in local ecosystem management projects, it has been confirmed that participation enhanced life satisfaction, improved health, and increased self-confidence [ 47 , 48 ]. Uehara and Itoh (1999) reported that long-term forest work performed over a period of 1 year improved the physical ability, communication skills, emotional stability, and daily life activities of disabled individuals [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this review is indicative of this area of the research in general in that many NT interventions have a physical activity component; this limits ability to identify the therapeutic impact of nature exposure alone and excludes potentially informative studies from this review. For example, a recent quantitative prospective study by Smyth et al (2022) involved a SP “Green Gym” intervention with 892 participants with MI and/or long-term conditions, and showed significant improvements in participant wellbeing, with greater improvements for participants with poorer baseline wellbeing. This study used the WEMWBS ( Stewart-Brown and Janmohamed, 2008 ) which is used in 2 included studies ( Wilson et al, 2011 ; Maund et al, 2019 ), and included an appropriately long 13-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being a rigorous study in a peer-reviewed journal it does not meet the inclusion criteria for this review due to its primary focus on physical activity. However, this intervention included many activities that overlap with those in this review, e.g., gardening, weeding, and learning about local species ( Smyth et al, 2022 ). It is also similar to that of Christie and Cole (2017) in which all activities are opt-in and range from learning about local species (very low physical activity requirements) to tree planting (high physical activity requirements).…”
Section: Discussionmentioning
confidence: 99%